FAB542: 3D Computer Animation Advance / College of Creative Arts - UiTM, College of Creative Arts (2023)
This course is an extension course of 3D Character Animation which emphasizes on the 3D animation techniques of facial expression and lip-synchronisation as well as advanced body gestures and movements. Students will learn to integrate the development of animated character and technical features of 3D animation software techniques and tools upon producing a completed animation project.